The Impacts of Hosting Major Sporting Events: Resident's Perceptions of the Mediterranean Games 2013 in Mersin - Dilek Atçı; Kamil Unur; Doğan Gürsoy (International Review of Management and Marketing, 2016)
This study investigates the residents' perceptions of the Mediterranean Games 2013. Data was collected by questionnaire survey of 1700 residents of Mersin by applying quota sampling.  A structural model to assess the factors on residents' perceptions of the impacts of the 2013 Mediterranean Games and how these perceptions affect their support is tested. The findings confirmed the five factor model that is consisted of economic benefits, economic costs, social benefits, social costs and image enhancement and revealed that there is a strong support for 17th Mediterranean Games. Image enhancement and economic benefits are the main factors that determine the residents' support.